UJI AKTIVITAS ANTIOKSIDAN DAUN BENALU KOPI (Loranthus Ferrugineus Roxb.) DENGAN METODE DPPH (1,1 – Difenil -2- Pikrilhidrazil) - Muammar Yulian; Safrijal Safrijal (UIN AR-RANIRY, 2018)
The study about antioxidant activity test of coffee parasite leaves (Loranthus ferrugineus Roxb.) by 1,1-diphenyl-2-pikrilhidrazyl (DPPH) method has been done. The aim of this study was to determine the content and activity of secondary metabolites, flavonoids and antioxidant, which found in the coffee parasite leaves. Dry powder of parasite coffee leaves (Loranthus ferrugineus Roxb.) as much as 0.5 kg were macerated by 2 L of ethanol solvent at room temperature for 4 x 24 hours, then mixed and filtered. Ethanol filtrate was evaporated at 30-40°C by using a rotary evaporator to obtain the crude extract of coffee parasite leaves. The results of the phytochemical screening showed positively that the extract was containing alkaloid, flavonoids, saponins, tannins and steroid compounds.The results of the antioxidant activity test by using DPPH method was obtained that the amount of antioxidant activity of the samples of ethanol extract had a very strong antioxidant activity against radical DPPH 0.05 mM, with IC50 values was obtained 6.063 ppm. Whereas, for comparison of ascorbic acid was about 3.127 ppm.